GDF15 is an exercise-induced hepatokine regulated by glucagon and insulin in humans - Plomgaard, Peter; Hansen, Jakob S.; Townsend, Logan K.; Gudiksen, Anders; Secher, Niels H.; Clemmesen, Jens O.; Støving, Rene K.; Goetze, Jens P.; Wright, David C.; Pilegaard, Henriette (Frontiers in Endocrinology, 2022)
Objective: Growth differentiation factor (GDF)-15 is implicated in regulation of metabolism and circulating GDF15 increases in response to exercise. The source and regulation of the exercise-induced increase in GDF15 is, however not known. Method: Plasma GDF15 was measured by ELISA under the following conditions: 1) Arterial-to-hepatic venous differences sampled before, during, and after exercise (n=10); 2) exogenous glucagon infusion compared to saline infusion in resting healthy subjects (n=10); 3) an acute exercise bout with and without a pancreatic clamp (n=6); 4) subjects fasting for 36 hours (n=17), and 5) patients with anorexia nervosa (n=25) were compared to healthy age-matched subjects (n=25). Tissue GDF15 mRNA expression was determined in mice in response to exhaustive exercise (n=16). Results: The splanchnic bed released GDF15 to the circulation during exercise and increasing the glucagon-to-insulin ratio in resting humans led to a 2.7-fold (P<0.05) increase in circulating GDF15. Conversely, inhibiting the exercise-induced increase in the glucagon-to-insulin ratio blunted the exercise-induced increase in circulating GDF15. Fasting for 36 hours did not affect circulating GDF15, whereas resting patients with anorexia nervosa displayed elevated plasma concentrations (1.4-fold, P<0.05) compared to controls. In mice, exercise increased GDF15 mRNA contents in liver, muscle, and adipose tissue. Conclusion: In humans, GDF15 is a “hepatokine” which increases during exercise and is at least in part regulated by the glucagon-to-insulin ratio. Moreover, chronic energy deprivation is associated with elevated plasma GDF15, which supports that GDF15 is implicated in metabolic signalling in humans.